2008
DOI: 10.1097/moo.0b013e3282fe96bd
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength training applications

Abstract: Respiratory muscle strengthening programs are either inspiratory or expiratory and are typically accomplished using handheld devices. Training durations typically examined have been 4-8 weeks. Training trials usually take 20-30 min per day. Training frequency varies across studies. Detraining outcomes are important to examine as part of clinical trials. Defining detraining outcomes has major implications for the development of a complete rehabilitation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 43 publications
2
35
0
1
Order By: Relevance
“…RESPIRATORY CARE • NOVEMBER 2014 VOL 59 NO 11protocols of expiration at 60% P Emax , 2 whereas in exercise programs of the upper limb, the FVC did not show any improvement. 3 No data have been obtained for this outcome in inspiratory therapies; therefore, it would be interesting to investigate this aspect in future studies.…”
Section: Respiratory Muscle Training In Patients With Msmentioning
confidence: 93%
See 4 more Smart Citations
“…RESPIRATORY CARE • NOVEMBER 2014 VOL 59 NO 11protocols of expiration at 60% P Emax , 2 whereas in exercise programs of the upper limb, the FVC did not show any improvement. 3 No data have been obtained for this outcome in inspiratory therapies; therefore, it would be interesting to investigate this aspect in future studies.…”
Section: Respiratory Muscle Training In Patients With Msmentioning
confidence: 93%
“…3 In another review, P Emax increases of 41 and 50% were found in a group of healthy people in training for 4 and 8 weeks, respectively. 11 It has been established that a protocol of 10 weeks at a frequency of 7 d/week with 3 sets of 15 inspirations produced a significant improvement in P Imax (P ϭ .003 4 and P Ͻ .001), 5 whereas no significant improvements in P Emax were observed. However, in other studies, improvements have been found in P Imax (P Ͻ .008) but in smaller proportion in protocols of 10 weeks but at 2 sessions/day with 3 sets of 10 inspirations and 1 min of rest between sets.…”
Section: What Is the Evidence For Respiratory Muscle Training With A mentioning
confidence: 99%
See 3 more Smart Citations